(untitled) (Fiep Bulletin - online, 2015)
Quality of life (QL) of the population depends on several influencing factors ranging from aspects of physical health to relationships with the social environment. We know that teachers are professionals who tend to deal with numerous factors that can impair their QL, given their workday, the typical problems in the area of education and dissatisfaction with salaries. Although there are few studies that have addressed the teachers on QL in general, there is a lack of data on specific QL of physical education teachers. Thus, the present study aimed to assess QL and the level of job satisfaction of physical education teachers working in primary schools in the city of Itumbiara-GO. The questionnaire used for QL was the short version WHOOQ applied to 40 teachers and supplementary data and job satisfaction, another questionnaire with nine questions addressed. The main results the following general averages were observed in the areas: physical (70,7), psychological (74,2), social (71,7) and environment (60), already the final average QL of all subjects was 49,1. It was concluded that among the areas calculated by WHOOQ the most committed among teachers was the environment and, in addition, the main complaints were the poor working conditions as the structural aspects of the school and the problems associated with managing group relations and other teachers in other areas.